The Dysfunctional Family in Toni Morrison's The Bluest Eye (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2023)
As the marginalized and minority group in America, Black people’s lives were under the control and influence of White hegemony. This condition affected their social, economic, and cultural activities. This study aims to identify the form of dysfunction in the family, the cause of dysfunction in the family, and the effect on children’s psychology. This study uses a descriptive qualitative method. The researchers use a novel written by Toni Morrison entitled The Bluest Eye as the primary source of data. Additionally, some books, journal articles, and relevant internet sources use as secondary sources. Then, the data was collected and analyzed in several steps. The result shows that the dysfunction in the family is in the form of maltreatment of the family members that are influenced by the pain of the parent’s childhood. It eventually leads to the way how they treat or build relationships with their children and others. The impact of this dysfunctional family on the children is that they become malicious and impulsive, and suffer from a mental disorder or schizophrenia.